Examining a social cognitive motivational model predicting university students’ iIntention to continue in competitive sports - Teng, Iris Swee Ting (2017)
The annual Institute-Varsity-Polytechnic Games (IVP) and Singapore University Games (SUniG) provides a platform for Singapore undergraduates to cultivate friendship and increase the standards of university sports. The purpose of this study is to investigate how the types of motivation, using the Self-determination Theory (SDT) (Deci & Ryan, 1985), can predict university student athletes’ intention to continue to participate in university sports competition. This association will be mediated by the major constructs of the Theory of Planned Behvaviour (TPB) (Ajzen, 1991). Data were collected using an online survey from 127 athletes from various Singapore universities. The survey included: a) the perceived locus of causality scale (PLOC) (Ryan and Connell, 1989), to assess the motives of the university student athletes; b) the TPB questionnaire (Ajzen, 2006) to assess their attitude, subjective norm, perceived behavioural control (PBC) and intention to continue to compete in university sports. Path analysis was conducted to examine the relationship and results revealed that autonomous motivation (AM) acts as superior constructs that influence undergraduates’ intention to continue to participate in university sports competition. However, this association must be mediated by attitude or subjective norm for a significant relationship which provides greater insights of how the types of motives can influence continuation intention. This study can be taken as a useful reference for sports coaches and practitioners towards enhancing student athletes’ AM, instilling the right beliefs, and shaping a positive attitude towards intention to continue to compete in university sports. The policies implemented by the Singapore government to develop and retain sports talent will only realize its full potential with utmost support from sports coaches and administrators to be effective.